Improving reading comprehension through the development of critical thinking of students at madrasah aliyah - Mustopa, Arif Zaenal; Sugirin, Sugirin (LingTera, 2020)
This research aims to develop the reading comprehension skills in English written texts of Grade XI students of Madrasah Aliyah Al-Ikhlash Cicalengka, Bandung through the development of critical thinking in teaching process. This research was collaborative classroom action research. The subjects were the 11th grade students of Madrasah Aliyah Al-Ikhlash Cicalengka, Bandung. The data were collected through pretest and posttest, observation, field notes, and interviews. The students were introduced with the concept of critical thinking starting with the concept of position, agreement, disagreement, and argument as well as the categorization of the opinion and fact in the text. Finally the students were asked to do some tasks and give their opinion related to the position of the writer and their background knowledge. The result showed that there was an improvement in teaching processes. In the first cycle, the students' involvement in classroom activity was improved. There were about 70% of the students who actively involved in the process and it increased in the second cycle. In expressing opinion, the students could actively express their opinion related to the text being discussed both in written and orally.  The improvement also occurred in students' reading comprehension skills score. The result of paired t-test showed that there was significant different in comparison of pretest and both posttests 1 and 2. The result showed that the significant value of 0.000 was smaller than the significant level of 0.05 or 5%. This means that the improvement was significant. The result proved that improving reading comprehension skills could be achieved by developing critical thinking in teaching reading process.